STRATEGI MENINGKATKAN SELF-LOVE PADA REMAJA YANG KURANG PERCAYA DIRI KARENA JERAWAT: STUDI KASUS DI KAMPUNG BADAMUSALAM KOTA SERANG - RAHMA, NADILA SITI; fina, Safinah; udin, amin; holisoh, siti; ramanda, peni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore strategies to improve self-love among adolescents who experience low self-confidence due to acne, focusing on the case of Putri Nur Intan in Kp. Badamusalam, Sawahluhur Village, Kasemen District, Serang City, Banten. The research uses a qualitative descriptive method through observation and interviews with the subject, her parents, and a guidance counselor. Results show that the application of positive affirmations, parental understanding, and peer support significantly increased self-love and confidence. This study contributes practical insights for school counselors and parents in addressing appearance-based psychological issues in adolescents.